Coronary angiography of the ex‐situ beating donor heart in a portable organ care system. Issue 7 (2nd November 2022) - Meredith, Thomas; Scheuer, Sarah; Hoffman, Michael; Joshi, Yashutosh; Kathir, Krishna; Gunalingam, Brendan; Roy, David; Wilson, Stephanie; Jansz, Paul; Macdonald, Peter; Muller, David
Abstract: Objectives: To determine safety and feasibility of ex‐situ coronary angiography. Background: To cater for the perpetually growing demand for heart donors, interest in donation following circulatory death (DCD) has been rekindled. Further pursuit of donor pool expansion has led to eligibility extension to "marginal" donors who are at higher risk of coronary artery disease (CAD). Excluding CAD in potentially eligible DCD donors, for whom ante‐mortem angiography is commonly not permitted, is therefore challenging. Ex‐situ coronary angiography serves as an ethical and feasible diagnostic tool to assess for preclusive CAD. Methods: We undertook a systematic review of the published literature and institutional retrospective review of case experience with ex‐situ coronary angiography of donor hearts, supported by a portable organ care system. Results: Combined literature and institutional case review yielded nine total cases of ex‐situ coronary angiography of donor human hearts plus one experimental porcine model. Of the eight cases of ex‐situ coronary angiography performed at our institute, all were conducted without complication or injury to the allograft. Two thirds of reported human cases have proceeded to successful transplantation. Conclusions: Diagnostic coronary angiography of the ex‐situ beating donor heart is safe, feasible, and demonstrates novel clinical utility in mitigating subsequent transplantation of unsuitable allografts. In the setting of suspected coronary atherosclerosis of the donor heart, which may preclude favorable transplantation outcomes, ex‐situ coronary angiography should be considered at eligible transplant centers.